2021
DOI: 10.1177/1748006x211047308
|View full text |Cite
|
Sign up to set email alerts
|

An AdaBoost-based tree augmented naive Bayesian classifier for transient stability assessment of power systems

Abstract: By focusing on the accuracy limitations of the naive Bayesian classifier in the transient stability assessment of power systems, a tree augmented naive Bayesian (TAN) classifier is adopted for the power system transient stability assessment. The adaptive Boosting (AdaBoost) algorithm is used in the TAN classifier to form an AdaBoost-based tree augmented naive Bayesian (ATAN) classifier for further classification performance improvement. To construct the ATAN classifier, eight attributes that reasonably reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Common traditional object detection algorithms include the Viola Jones detector [13], the HOG detector [14], and the component-based deformable model (DPM) [15]. Of these, the Viola Jones detector is mainly composed of three parts: Harr features [16], Adaboost classifier [17], and cascaded classifier. Because Harr features are relatively simple features, the classifier is prone to overfitting, which leads to low robustness of the algorithm.…”
Section: Related Work 21 Object Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common traditional object detection algorithms include the Viola Jones detector [13], the HOG detector [14], and the component-based deformable model (DPM) [15]. Of these, the Viola Jones detector is mainly composed of three parts: Harr features [16], Adaboost classifier [17], and cascaded classifier. Because Harr features are relatively simple features, the classifier is prone to overfitting, which leads to low robustness of the algorithm.…”
Section: Related Work 21 Object Detectionmentioning
confidence: 99%
“…where w is the weight learned by the feature, and I i is the input feature map, taking the stable numerical coefficient ε = 0.0001. The fusion process of the two features in the middle layer is shown in Equations ( 16) and (17).…”
Section: Bidirectional Feature Fusion Networkmentioning
confidence: 99%
“… 23 , 24 , 25 The most commonly used methods related to ensemble learning are Bagging 26 and Boosting, 27 , and AdaBoost is the mainstream algorithm of Boosting. 28 Scholars often apply these methods to many different fields, such as target prediction, 29 error detection, 30 image recognition, 31 and text classification. 32 , 33 For example, Yang et al 31 used the AdaBoost algorithm to achieve the classification of precipitation types using radar map data.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Li 6 develop classification methods, which were originally developed by researchers from the machine learning research community, to assess the transient stability of power systems. They found that the AdaBoost-based tree augmented naive Bayesian classifier can significantly improve the classification performance of the transient stability assessment of the power system.…”
mentioning
confidence: 99%